2019
DOI: 10.3389/fphar.2019.01183
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Scinderin Expression Correlates With Liver Metastasis and Poor Prognosis in Colorectal Cancer

Abstract: Many genes and mutations have been reported for colorectal cancer (CRC); however, very few have been associated with colorectal cancer liver metastasis (CRLM). We performed gene expression profiling experiments to identify genetic markers for CRLM and elucidate the molecular mechanisms. Microarray experiments were performed on CRC primary tumor samples with or without liver metastasis (LM) using the Affymetrix U133 plus 2.0 GeneChip Array. A new identified gene-scinderin (SCIN) was overexpressed with synchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Gelsolin has been found to regulate EMT in HPV cells, predict patient prognosis in squamous cell carcinoma of the larynx, and suppress apoptotic machinery in neuroendocrine prostate cancer [42,43]. Adseverin expression has been reported to be a marker for cisplatin resistance in bladder cancer and correlate with prognosis in colorectal cancer [44,45]. Calcium signaling is disrupted in GBM, and may provide an abundant source for gelsolin family member activation [46].…”
Section: Advillin Family Members and Their Association With Cancermentioning
confidence: 99%
“…Gelsolin has been found to regulate EMT in HPV cells, predict patient prognosis in squamous cell carcinoma of the larynx, and suppress apoptotic machinery in neuroendocrine prostate cancer [42,43]. Adseverin expression has been reported to be a marker for cisplatin resistance in bladder cancer and correlate with prognosis in colorectal cancer [44,45]. Calcium signaling is disrupted in GBM, and may provide an abundant source for gelsolin family member activation [46].…”
Section: Advillin Family Members and Their Association With Cancermentioning
confidence: 99%
“…In this context, serpinA1 may be a potential therapeutic target for novel predictive biomarkers and CRC. Scinderin (SCIN) may be a significant predictor of poor prognosis in patients with CRC liver metastasis (CRLM) and CRC [ 53 ]. Our research provided new insights into the genes highly expressed in CRC, which may help explain the dual role of Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that SCIN is highly expressed in human prostate cancer specimens and human lung cancer tissues and plays an important role in cell proliferation (Liu et al, 2015; Wang et al, 2014). In colorectal cancer, the expression of SCIN is increased and is closely related to poor prognosis (Lin, Li, et al, 2019). Therefore, it may be a potential therapeutic target in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%